To what extent does frailty mediate the association between age and the outcomes of brain reperfusion following acute ischemic stroke? - Miranda, Luana Aparecida; Luvizutto, Gustavo José; Bessornia, Pedro Augusto Cândido; Furlan, Natalia Eduarda; Winckler, Fernanda Cristina; Ferreira, Natalia Cristina; Hamamoto Filho, Pedro Tadao; de Souza, Juli Thomaz; Martin, Luis Cuadrado; Zanati Bazan, Silméia Garcia; Pinheiro Modolo, Gabriel; de Freitas, Carlos Clayton Macedo; et al. (Frontiers in Aging Neuroscience, 2024)
Objective: We evaluated the extent to which frailty mediated the association between age, poor functional outcomes, and mortality after acute ischemic stroke when patients were treated with brain reperfusion (thrombolytic therapy and/or thrombectomy).This retrospective cohort study included patients diagnosed with ischemic stroke who had undergone intravenous cerebral reperfusion therapy and/or mechanical thrombectomy. We created a mediation model by analyzing the direct natural effect of an mRS score >2 and death on age-mediated frailty according to the Frailty Index.We enrolled 292 patients with acute ischemic stroke who underwent brain reperfusion. Their mean age was 67.7 ± 13.1 years. Ninety days after the stroke ictus, 54 (18.5 %) participants died, and 83 (28.4 %) lived with moderate to severe disability (2 < mRS < 6). In the mediation analysis of the composite outcome of disability (mRS score > 2) or death, frailty accounted for 28 % of the total effect of age. The models used to test for the interaction between age and frailty did not show statistically significant interactions for either outcome, and the addition of the interaction did not significantly change the direct or indirect effects, nor did it improve model fit.Frailty mediated almost one-third of the effect of age on the composite outcome of disability or death after acute ischemic stroke.